Effect of Eu3+ on the morphology, structural, optical, magnetic, and photocatalytic properties of ZnO nanoparticles. (November 2018) - Poornaprakash, B.; Chalapathi, U.; Sekhar, M. Chandra; Rajendar, V.; Vattikuti, S.V. Prabhakar; Pratap Reddy, M. Siva; Suh, Youngsuk; Park, Si-Hyun
Abstract: In this study, we attempted to synthesize ZnO nanoparticles with various Eu 3+ doping concentrations by a simple coprecipitation method for multifunctional applications. Morphology studies of the synthesized samples revealed the presence of hexagonal-shaped and monodispersed particles. A slight shift in the X-ray diffraction patterns of the Eu 3+ -doped ZnO samples confirmed the successful incorporation of the dopant ions into the host crystal. A change in the E2 (high)-mode intensity was ample evidence of intrinsic defects associated with the oxygen atoms. Diffuse reflectance spectroscopy studies provided sufficient evidence of tuning of the bandgap of ZnO by Eu 3+ doping, with a typical red shift. X-ray photoelectron spectroscopy studies revealed the presence of Eu with a +3 state in the ZnO lattice. All the doped ZnO nanoparticles exhibited typical room-temperature ferromagnetism (RTFM). The Eu 3+ -doped samples displayed a higher photocatalytic degradation (PCD) of RhB dye under UV light illumination compared with the undoped ZnO nanoparticles. Thus, Eu 3+ doping is an effective approach for enhancing the RTFM and PCD properties of ZnO for spintronic and photocatalytic applications. Highlights: Eu 3+− doped ZnO NPs were synthesized by a simple co-precipitation method. Eu 3+ -doped NPs NPs displayed RTFM as a function of doping concentration. Eu 3+ -doped NPs exhibited a higher PCD of RhB dye than undoped ZnO NPs. Eu 3+ doping is an effective way for enhancing the RTFM and PCD of ZnONPs.